Analysis of spatial and temporal variations of NDVI and its driving factors in the corridor of Lan-Xin railway - Chen, Xingshan; Yan, Qingwu; Yi, Minghao; Ma, Xiaosong; Li, Guie; Wu, Zihao; Pan, Qinke; Qiu, Yong (Frontiers in Environmental Science, 2024)
Vegetation is the main factor of ecological stability, but the construction of large-scale corridor projects will bring some damage to vegetation. Based on the NDVI, temperature and precipitation data of the growing season from 1990 to 2021 (June to September), this paper uses the maximum synthesis method, trend analysis method, correlation analysis method and coefficient of variation method to study the spatial-temporal changes and driving factors of NDVI in the past 32 years, taking the 30km belt buffer zone along the Lan-Xin Railway as the research area.The influence range of railway construction on NDVI in different climatic conditions is analyzed.The results showed that: (1) From 1990 to 2021, the average annual temperature of the growing season in the study area showed an increasing trend, the average annual precipitation showed a decreasing trend, and the average annual NDVI showed an increasing trend; NDVI was positively correlated with temperature in 54.04%, and positively correlated with precipitation in 62.88%. Precipitation had a greater effect on NDVI than temperature. (2) Under the same climatic conditions, the NDVI variability coefficient in the study area fluctuates significantly within 3000-21000 meters along the railway line, stabilizing beyond 21000 meters; the impact range of railway construction on NDVI gradually increases with increasing precipitation within the same temperature range, and increases gradually with rising temperatures within the same precipitation range. (3) During the growing season (June to September) in the study area, when the temperature is below 25°C, NDVI increases initially with increasing precipitation before decreasing, showing an overall upward trend; when the temperature is above 25°C, NDVI initially increases with increasing precipitation before decreasing. High temperature and high precipitation will inhibit vegetation growth and reduce NDVI. The NDVI of the core area before the railway construction is larger than that of the background area, while the NDVI of the core area after the railway construction is smaller than that of the background area. In short, the construction of Lan-Xin Railway has a certain influence on NDVI along the line.